Unpacking the opportunities and challenges in learning speaking online during Covid-19 outbreak: A case-study of Indonesian EFL college students - Syafrayani, Putri Rizki; Ginting, Pirman; Hasnah, Yenni; Saragih, Mandra (Englisia Journal, 2022)
The challenges brought by Covid-19 have threatened not only the economy and health fields but also the educational sectors. In light of education, this issue has led to the swift migration of the learning process from conventional mode to online learning which has resulted in another bottleneck. The current study explores the perception of EFL Indonesian college students about the challenges and benefits of learning speaking through the online system during the Covid-19 outbreak. Forty-five college students participated in this study and were inquired through a semi-structured questionnaire in the weeks following the final term examinations for the academic year 2020-2021. The data was probed by using grounded theory proposed by Creswell. The findings exposed that effectiveness, online benefits, and improvement opportunities were the benefits obtained by students from the online learning. Meanwhile, distraction and information overload, a technical error in online learning technology and internet connectivity matters as well as limited interaction and inadequate support were hindrances that often hampered the students.  Consequently, this scholarly paper also provides advice on the essence of the readiness of adequate facilities and the collaboration from stakeholders; government, teachers, students, and parents to successfully implement online learning.